2012
DOI: 10.1016/j.juro.2012.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Fatigue: Impact of Case Order on Perioperative Parameters and Patient Outcomes

Abstract: Despite concern that surgeon fatigue may impact outcomes, our data suggests that performing several complex urological procedures consecutively is not associated with worse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…These results are consistent with what was found in the previous studies [ 6 , 9 ]. However, they are very different from those of Bagrodia et al [ 24 ] and Uchal et al [ 5 ], who detailed that fatigue and performance are covariates. Increase in errors and time to complete laparoscopic task is more likely to be caused by trainee during acclimatization; however, as more and more trials are performed, the learning curve increases, which gradually decreases errors and completion time.…”
Section: Discussioncontrasting
confidence: 79%
“…These results are consistent with what was found in the previous studies [ 6 , 9 ]. However, they are very different from those of Bagrodia et al [ 24 ] and Uchal et al [ 5 ], who detailed that fatigue and performance are covariates. Increase in errors and time to complete laparoscopic task is more likely to be caused by trainee during acclimatization; however, as more and more trials are performed, the learning curve increases, which gradually decreases errors and completion time.…”
Section: Discussioncontrasting
confidence: 79%
“…It may be attributed to physicians fatigue after several hours' work. However, other studies revealed that whether the surgeons had performed other surgeries prior to complex liver resection [8] or prostatectomy [18] in the same day did not affect the perioperative outcome.…”
Section: Discussionmentioning
confidence: 95%
“…As the attending always exclusively performed the first case of the day due to operative room availability, our results may have been subject to the potentially confounding effect of surgeon fatigue. Bagrodia et al 18 showed that operative times, intraoperative complications, and oncological and functional outcomes were similar regardless of order of RARP. However, the authors only compared outcomes between the first and second RARP cases of each day, and so the implications of surgeon fatigue on five consecutive RARPs (our typical operative day) is still unclear.…”
Section: Discussionmentioning
confidence: 99%